Self-Mixing Signal Characteristics of Complex-Coupled Distributed-Feedback Terahertz Quantum-Cascade Lasers - Ge, Lei; Yang, Ning; Wang, Jian; Chu, Weidong; Duan, Suqing; Xie, Yan; Wang, Yingxin; Li, Lianhe; Linfield, Edmund (Frontiers in Physics, 2021)
Self-mixing interference (SMI) in terahertz quantum cascade lasers (THz QCLs) is one of the significant approaches for coherent THz imaging and sensing techniques. Here, the output characteristics of SMI in distributed feedback (DFB) THz QCLs from the index- to the gain coupling regimes are studied using the coupled wave theory and the multi-mode rate equation method. A mode hopping phenomenon is found to occur when the DFB coupling factor changes from index-coupling to gain-coupling, and the characteristics of the self-mixing signals of DFB-QCLs change greatly with this mode hopping. With the modulus of the coupling factor fixed and its argument varied from 0 to pi/2, an extreme point of the self-mixing frequency and power signals of DFB-QCLs is found at pi/9 due to the mode hopping. For index-coupling dominated DFB-QCLs, the amplitudes of both the self-mixing frequency and power signals increase with increasing DFB coupling factor argument. For gain-coupling dominated DFB-QCLs, with increasing argument value, the amplitude of the self-mixing power signal increases, but the amplitude of the self-mixing frequency signal decreases. With the argument of the coupling factor fixed, we also found that the amplitudes of the self-mixing frequency signals decrease with increasing modulus for both index-coupling dominated and gain-coupling dominated DFB-QCLs. For index-coupling dominated DFB-QCLs, the amplitudes of the self-mixing power signals decrease with increasing modulus; however, the amplitudes of the self-mixing power signals of gain-coupling dominated DFB-QCLs increase. With the argument of the coupling factor fixed, for index-coupling dominated DFB-QCLs, we found that the amplitudes of both the self-mixing frequency and power signals decrease with the increasing modulus. For gain-coupling dominated DFB-QCLs, with the coupling factor modulus increasing, the amplitudes of the self-mixing frequency signals decrease, however, the amplitudes of the self-mixing power signals increase. These results may help with the application of DFB-QCLs to self-mixing interferometers.